Data Encoding Improvement and Size Reduction of Chipless RFID Tag Using Short-Circuit Line Effect and Angle-Based Divided Loops - Nguyen, Thanh Huong; Tran, Duc Quang (Old Journal, 2020)
This paper focuses on a short circuit and concentric loop effects to improve the structure dimension as well as enhance the ability to encode electromagnetic wave data for chipless RFID tags. The tag is composed of star-shaped rings that are concentrically nested together. The following factors help reduce the tag size: using the phenomenon of electromagnetic backscattering, assessment by the Radar Cross Section (RCS), the antenna-free tag only includes the multi-frequency resonators. By inserting short circuit lines combined with concentric loops, the number of resonant peaks increases exponentially without increasing the tag overall dimension. In addition, by inserting the short circuit lines at different angles between the two consecutive loops, we can adjust the resonant frequency in the frequency bands, thereby changing the value of the bit by shifting the frequency position. The overall dimension of the resulted tag is 13mm×13 mm and the tag is aimed to be a printable tag on the flexible substrate to minimize the fabrication cost. With the 18-vertex star-shaped tag with five concentric loops, this chipless RFID tag can encode up to 16 bits with high resolution and large data density.